Potential for Nirsevimab use in Pakistan - Muhammad Moaz; Basum Hayat (Journal of the Pakistan Medical Association)
Respiratory Tract Infections can be classified as upper and lower tract infections. Upper tract infections are more common such as laryngitis and pharyngitis, but the infections of lower respiratory tract are more fatal such as influenza or bronchitis. Respiratory Syncytial Virus (RSV) is one of the major causes of acute lower respiratory tract infections and consequent admissions to hospital among young children. This virus belongs to paramyxoviridae family and is an RNA virus. It can cause a range of respiratory symptoms such as cold-like symptoms to more severe respiratory distress and complications such as bronchiolitis and pneumonia. It spreads through respiratory droplets when an individual infected with it, coughs, or sneezes. Preterm infants are highly susceptible to RSV infection due to weak immune system.